Source apportionment and health risk assessment of polycyclic aromatic hydrocarbons (PAHs) in the coastal ecosystem of the Brunei Bay, Brunei - Sharifi, Reza; Keshavarzifard, Mehrzad; Sharifinia, Moslem; Zakaria, Mohamad Pauzi; Mehr, Meisam Rastegari; Abbasi, Sajjad; Yap, Chee Kong; Yousefi, Mohamad Reza; Masood, Najat; Magam, Sami Muhsen; Alkhadher, Sadeq Abdullah Abdo; Daliri, Moslem (Elsevier, 2022)
Pollution characteristics and associated ecological risks of PAHs in sediments from Brunei Bay, Brunei were investigated. The concentrations of ∑16 PAHs ranged from 826.7 to 2955.3 μg kg− 1 , indicating moderate to high level of pollution. Source apportionment of PAHs by molecular isomeric ratios and positive matrix factorization model indicated impact of potential anthropogenic PAH sources including combustion of biomass and fossil fuels. The data indicated relatively no significant ecotoxicological risk for most of PAH compounds. To estimate the individual c-PAH toxicity, the toxic equivalent quantity (c-TEQ) was calculated. Results of the TEQ analysis showed that BaP followed by DBA and BaA are the most carcinogenic of PAHs examined in the study area. The evaluation of human health risk of PAHs revealed that the cancer risk of PAHs for adults and children was higher than the USEPA threshold (<1E− 06) and lower than 1E-3, implying low to moderate risk.